Isolated posterior malleolus fractures: A systematic review - Farrar, Nicholas; Nakken, Erik; Walley, Kempland; Talusan, Paul (Journal of the Foot & Ankle, 2026)
Objective: To clarify the mechanism, evaluation, surgical indications, and outcomes of isolated posterior malleolus fractures without additional osseous injury. Methods: A systematic review was conducted using PubMed, Cochrane, and EMBASE databases from their inception to March 31, 2023, focusing on isolated posterior malleolus fractures. Inclusion criteria included adult patients (≥ 18 years old), full-text articles, and studies on isolated posterior malleolus fractures. Results: Of 1,193 screened articles, 25 met the inclusion criteria, comprising 117 patients. Among them, 28 (23.9%) underwent surgery, while 89 (76.1%) received non-operative treatment. Common surgical indications included fragment size, displacement, and syndesmotic instability. Two studies (n = 41) of non-operative management reported three cases of osteoarthritis at long-term follow-up. Conclusion: Current literature on isolated posterior malleolus fractures is limited to case reports and small series. Diagnosis can be challenging, but accurate identification is crucial, as some patients benefit from surgical intervention. Non-operative management remains the standard approach, with excellent long term functional outcomes; however, larger cohort studies with longer follow-up are needed to strengthen current knowledge. Level of Evidence: Level IV; Therapeutic Studies- investigating the results of treatment; Systematic Review of Level III & IV Studies